Preparation method of catalyst for improving low-temperature ignition performance of gasoline car emission

By applying a double-layer coating on the metal honeycomb carrier and optimizing the precious metal formula, the problem of substandard cold start emissions of gasoline vehicles is solved, and the low-temperature ignition performance and pollutant conversion rate are improved. It is suitable for low-temperature cold start emission control of gasoline vehicles and the after-sales modified vehicle market.

CN120618462AInactive Publication Date: 2025-09-12CHENGDU SANHEYUAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510747897.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2025-09-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing technology, the cold start emissions of gasoline vehicles do not meet regulatory requirements. Especially under low temperature conditions, the ignition efficiency of metal honeycomb carrier catalysts is insufficient and the cost is high.

Method used

A double-layer coating is applied on the surface of the metal honeycomb carrier. The bottom coating contains composite cerium-zirconium oxide, γ-Al2O3 and precious metals, and the upper coating contains composite cerium-zirconium oxide, γ-Al2O3 and a variety of precious metals. The precious metal formula is optimized to reduce usage through loading and calcination treatment through a specific process.

Benefits of technology

It significantly reduces the ignition temperature of the catalyst, improves the pollutant conversion rate, reduces the use of precious metals, and reduces costs. It is suitable for industrial mass production and the after-sales modified vehicle market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120618462A_ABST
    Figure CN120618462A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a catalyst for improving low-temperature ignition performance of gasoline car emission, and relates to the technical field of catalysts.The preparation method comprises the following steps that the surface of a metal honeycomb carrier substrate is sequentially coated with a bottom coating and an upper coating; the bottom coating comprises a composite cerium zirconium oxide, gamma-Al2O3, a noble metal active component Pt and / or Pd, hydrosol and strontium acetate; the upper coating comprises composite cerium zirconium oxide, gamma-Al2O3, at least two of precious metal active components Pt, Pd and / or Rh, hydrosol and strontium acetate; the catalyst has great advantages in the aspects of low-temperature light-off activity and pollutant conversion efficiency, the performance reliability and stability of the low-temperature light-off activity and the pollutant conversion rate are also shown when the usage amount of precious metal is reduced, the linkage effect is generated by optimizing the formula of the precious metal, the usage amount of the precious metal is reduced, and the cost is reduced. The purposes of improving the product performance, reducing the cost and saving expensive resources can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions. Background Art

[0002] With the increasing number of vehicles on the road and production volume, and increasingly stringent environmental regulations, the cold start emissions of some vehicles in use do not meet regulatory requirements for various reasons and cannot pass exhaust gas inspections.

[0003] At present, the solution in the industry is generally to achieve the low-temperature ignition efficiency problem by replacing ceramic honeycomb carriers or metal honeycomb carriers with thinner pore walls. Ceramic honeycomb carriers are mostly imported products, most of which are expensive, and metal honeycomb carriers are superior to ceramic honeycomb carriers due to their advantages such as shock resistance, heat resistance, and price. The after-sales market has good feedback on metal honeycomb carrier catalysts, and the demand has increased year by year in recent years. Therefore, the present invention proposes a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions to solve the problems existing in the prior art. Summary of the Invention

[0004] In response to the above problems, the present invention proposes a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions. The method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions is beneficial to improving the low-temperature ignition effect of metal carrier catalysts, thereby significantly reducing the ignition temperature of the catalyst, and performs excellently in terms of the conversion rate performance of pollutants.

[0005] To achieve the purpose of the present invention, the present invention is implemented by the following technical solution: a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions, comprising the following steps:

[0006] Applying a bottom coating and an upper coating on the surface of the metal honeycomb carrier substrate in sequence;

[0007] The bottom coating comprises composite cerium-zirconium oxide, γ-Al2O3, noble metal active components Pt and / or Pd, hydrosol and strontium acetate;

[0008] The upper coating layer comprises composite cerium-zirconium oxide, γ-Al2O3, at least two of the noble metal active components Pt, Pd and / or Rh, a hydrosol and strontium acetate;

[0009] The coated metal honeycomb carrier is dried and calcined to obtain the catalyst.

[0010] A further improvement is that the slurry preparation of the bottom coating and the upper coating includes the following steps:

[0011] The composite cerium-zirconium oxide, γ-Al2O3 and aqueous sol dispersion are mixed and ground to form a carrier dispersion; the noble metal active component solution is loaded into the carrier dispersion to prepare a bottom slurry and an upper slurry respectively;

[0012] The total amount of precious metals in the bottom slurry accounts for 20-50% wt of the total amount of precious metals in the catalyst, and in the upper slurry accounts for 50-80% wt.

[0013] A further improvement is that the hydrosol dispersion is a modified aluminum substrate hydrated colloid, the mass concentration of which is 5-15% wt, and accounts for 5-15% wt of the total mass of the bottom slurry and the upper slurry.

[0014] A further improvement is that the bottom coating has an oxide solid content of 35-38% wt, comprising: 0.5-2% wt strontium acetate, 38-85% wt composite cerium-zirconium oxide, 15-60% wt γ-Al2O3, 1-5% wt cerium acetate, 5-12% wt hydrosol, and 0.1-2% wt Pt and / or Pd;

[0015] The oxide solid content of the upper coating is 25-33% wt, comprising: 0.5-2% wt strontium acetate, 38-85% wt composite cerium zirconium oxide, 15-60% wt γ-Al2O3, 6-15% wt hydrosol, and 0.1-3% wt of at least two of Pt, Pd, and Rh.

[0016] A further improvement is that the mass ratio of the components of the composite cerium-zirconium oxide is: CeO2 20-60%, ZrO2 40-70%, La2O3 3-6%, Nd2O3 0-5%, Y2O3 2-5%.

[0017] A further improvement is that the mass ratio of the γ-Al2O3 components is: La2O3 2-10%, Al2O3 90-98%.

[0018] A further improvement is that the oxide loading of the bottom slurry coated on the metal honeycomb carrier is 60-100 g / L, the oxide loading of the upper slurry after coating is 50-90 g / L, and the total coating oxide amount is 110-180 g / L.

[0019] A further improvement is that the noble metal active component is loaded onto the composite cerium zirconium oxide and γ-Al2O3 carrier by dripping method, and the noble metal in the bottom slurry is a single component of Pt or Pd, and the upper slurry is a combination of at least two of Pt, Pd, and Rh.

[0020] A further improvement is that the bottom layer slurry and the upper layer slurry also contain zirconium acetate, and the proportion of zirconium acetate oxide in the bottom layer coating and the upper layer coating is 1-5% by weight.

[0021] A further improvement is that the calcination treatment conditions are: drying temperature 80-150° C., calcination temperature 400-600° C., and calcination time 2-6 hours.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention improves the low-temperature ignition effect of metal-supported catalysts to significantly reduce the ignition temperature of the catalysts and exhibits excellent performance in terms of pollutant conversion efficiency. Specifically, the present invention includes a double-layer slurry preparation method, a double-coating coating process, and process control; wherein the bottom coating layer is composed of at least one precious metal of platinum and palladium in a specific ratio, and is loaded onto a composite cerium-zirconium powder or γ-Al2O3 substrate material in a specific manner; secondly, the top coating layer comprises a combination of at least two precious metals of platinum, palladium, and rhodium, and is loaded onto a composite CeO2 or γ-Al2O3 substrate material in a specific manner; and the total precious metal content is 3 to 25 g / cft. 3 , the mass ratio of Pt / Pd / Rh is 2~20:5~15:1~2; the coating of metal honeycomb carrier is easy to operate, the process can be quantified and standardized, which is suitable for industrial mass production, and has a wide range of applications in low-temperature cold start emission control of gasoline vehicles and after-sales modified vehicle market.

[0024] 2. The present invention has great advantages in low-temperature ignition activity and pollutant conversion efficiency. When the use of precious metals is reduced, the performance reliability and stability of low-temperature ignition activity and pollutant conversion rate are also demonstrated. By optimizing the precious metal formula, a linkage effect is generated to reduce the use of precious metals, thereby achieving the goals of improving product performance, reducing costs, and saving expensive resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Flowchart of the present invention. DETAILED DESCRIPTION

[0026] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the examples. The examples are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0027] Example 1

[0028] according to Figure 1 As shown, this embodiment proposes a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions, comprising the following steps:

[0029] A platinum nitrate solution containing 2.06 g of platinum was diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, with a composition of 20% CeO2-70% ZrO2-5% La2O3-5% Y2O3) at a rate of 5 ml / min to prepare A;

[0030] A platinum nitrate solution containing 1.375 g of platinum was diluted with deionized water and added dropwise to the stirred γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) at a rate of 5 ml / min to prepare B;

[0031] Take a platinum nitrate solution containing 0.25g of platinum and a rhodium nitrate solution containing 0.18g of rhodium, dilute it with deionized water, and add it dropwise to the stirred γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) at a rate of 5ml / min to prepare C;

[0032] A platinum nitrate solution containing 0.59 g of platinum and a rhodium nitrate solution containing 0.42 g of rhodium were diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, with a composition of 20% CeO2-70% ZrO2-5% La2O3-5% Y2O3) at a rate of 5 ml / min to prepare D;

[0033] Take 400g of pure water, slowly add 40g of modified pseudo-boehmite (preferably from Shan Aluminum, brand HV-D-03) under stirring, and stir at room temperature for 30min to prepare E;

[0034] 531 g of pure water was added with 15 g of strontium acetate, and the previously prepared A and B were added under stirring. After stirring for 10 min, 14.6 g of cerium acetate, 67.5 g of zirconium acetate, and 148.5 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 min (particle size D50 = 5-6 μm), and the pH was adjusted to 3.5-4.0 to prepare a bottom slurry F.

[0035] 862 g of pure water was added with 16.5 g of strontium acetate, and the previously prepared C and D were added under stirring. After stirring for 10 min, 56.1 g of zirconium acetate and 185 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 min (particle size D50 = 5-6 μm), and then the pH was adjusted to 3.5-4.0 to obtain the upper slurry G.

[0036] A Φ20mm*30mm*300 mesh metal support was coated with bottom slurry F at a wet weight gain of 164 g / L. The support was dried at 150°C with air blast. After cooling, top slurry G was applied at a wet weight gain of 205 g / L. The support was heated to 550°C in air at a rate of 3°C / min and calcined for 3 hours to obtain sample HC-1 for testing.

[0037] Example 2

[0038] according to Figure 1 As shown, this embodiment proposes a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions, comprising the following steps:

[0039] A platinum nitrate solution containing 0.827 g of platinum was diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, composition 40% CeO2-50% ZrO2-4% La2O3-2% Y2O3-4% Nd2O3) at a rate of 5 ml / min to prepare A;

[0040] A platinum nitrate solution containing 0.47 g of platinum was diluted with deionized water and added dropwise to the stirred γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) at a rate of 5 ml / min to prepare B;

[0041] Take a platinum nitrate solution containing 0.25g of platinum and a rhodium nitrate solution containing 0.07g of rhodium, dilute with deionized water, and dropwise add γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) in a stirred state at a rate of 5ml / min to prepare C;

[0042] A platinum nitrate solution containing 0.59 g of platinum and a rhodium nitrate solution containing 0.17 g of rhodium were diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, with a composition of 40% CeO2-50% ZrO2-4% La2O3-2% Y2O3-4% Nd2O3) at a rate of 5 ml / min to prepare D;

[0043] Take 400g of pure water, slowly add 40g of modified pseudo-boehmite (preferably from Shan Aluminum, brand HV-D-03) under stirring, and stir at room temperature for 30min to prepare E;

[0044] 635 g of pure water was added with 15 g of strontium acetate, and the previously prepared A and B were added under stirring. After stirring for 10 min, 14.6 g of cerium acetate, 67.7 g of zirconium acetate, and 149 g of the previously prepared E were added in sequence. The mixture was ground in a grinder for 15 min (particle size D50 = 5-6 μm) and the pH was adjusted to 3.5-4.0 to prepare a bottom slurry F.

[0045] 916 g of pure water was added with 16.5 g of strontium acetate, and the previously prepared C and D were added under stirring. After stirring for 10 min, 56 g of zirconium acetate and 185 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 min (particle size D50 = 5-6 μm), and then the pH was adjusted to 3.5-4.0 to obtain the upper slurry G.

[0046] A Φ20 mm*30 mm*300 mesh metal support was coated with bottom slurry F at a wet weight gain of 164 g / L. The support was dried at 150°C with air blast. After cooling, the top slurry G was coated at a wet weight gain of 205 g / L. The support was heated to 550°C in air at a rate of 3°C / min and calcined for 3 hours to obtain sample HC-2 for testing.

[0047] Example 3

[0048] according to Figure 1 As shown, this embodiment proposes a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions, comprising the following steps:

[0049] A platinum nitrate solution containing 0.86 g of platinum and a palladium nitrate solution containing 1.07 g of palladium were diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, composition 40% CeO2-50% ZrO2-4% La2O3-2% Y2O3-4% Nd2O3) at a rate of 5 ml / min to prepare A;

[0050] Take a platinum nitrate solution containing 0.57g of platinum and a palladium nitrate solution containing 0.7g of palladium, dilute with deionized water, and add dropwise 359g of γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) in a stirring state at a rate of 5ml / min to prepare B;

[0051] Take a platinum nitrate solution containing 0.3g of platinum and dilute it with deionized water. Add it dropwise to the stirred γ-Al2O3 (preferably from Baidexin, with a composition of 5% La2O3-95% Al2O3) at a rate of 5ml / min to prepare C;

[0052] A rhodium nitrate solution containing 0.3 g of rhodium was diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, with a composition of 40% CeO2-50% ZrO2-4% La2O3-2% Y2O3-4% Nd2O3) at a rate of 5 ml / min to prepare D;

[0053] Take 400g of pure water, slowly add 40g of modified pseudo-boehmite (preferably from Shan Aluminum, brand HV-D-03) under stirring, and stir at room temperature for 30min to prepare E;

[0054] 688 g of pure water was added with 13.6 g of strontium acetate, and the previously prepared A and B were added under stirring. After stirring for 10 minutes, 13.2 g of cerium acetate, 62 g of zirconium acetate, and 68 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 minutes (particle size D50 = 5-6 μm) and then the pH was adjusted to 3.5-4.0 to prepare a bottom slurry F.

[0055] 944 g of pure water was added with 11 g of strontium acetate, and the previously prepared C and D were added under stirring. After stirring for 10 min, 39 g of zirconium acetate and 114 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 min (particle size D50 = 5-6 μm), and then the pH was adjusted to 3.5-4.0 to obtain the upper slurry G.

[0056] Use the bottom layer slurry F to coat a Φ20mm*30mm*300 mesh metal carrier, control the wet weight gain to 164g / L, and dry it with air at 150℃. After cooling, coat it with the top layer slurry G, control the wet weight gain to 205g / L, and heat it in an air atmosphere at a rate of 3℃ / min to 550℃ and keep it at this temperature for 3 hours to obtain sample HC-3 for testing.

[0057] Example 4

[0058] according to Figure 1 As shown, this embodiment proposes a method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions, comprising the following steps:

[0059] A palladium nitrate solution containing 2.7 g of palladium was diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, composition 40% CeO2-50% ZrO2-4% La2O3-2% Y2O3-4% Nd2O3) at a rate of 5 ml / min to prepare A;

[0060] Take a palladium nitrate solution containing 1.52g of palladium and dilute it with deionized water. Add γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) in a stirring state at a rate of 5ml / min to prepare B;

[0061] Take a palladium nitrate solution containing 0.35g of palladium and a rhodium nitrate solution containing 0.177g of rhodium, dilute with deionized water, and dropwise add γ-Al2O3 (preferably manufactured by Baidexin, with a composition of 5% La2O3-95% Al2O3) in a stirred state at a rate of 5ml / min to prepare C;

[0062] A palladium nitrate solution containing 0.826 g of palladium and a rhodium nitrate solution containing 0.413 g of rhodium were diluted with deionized water and added dropwise to a stirred cerium-zirconium complex (preferably manufactured by Solvay, with a composition of 40% CeO2-50% ZrO2-4% La2O3-2% Y2O3-4% Nd2O3) at a rate of 5 ml / min to prepare D;

[0063] Take 400g of pure water, slowly add 40g of modified pseudo-boehmite (preferably from Shan Aluminum, brand HV-D-03) under stirring, and stir at room temperature for 30min to prepare E;

[0064] 648 g of pure water was added with 15 g of strontium acetate, and the previously prepared A and B were added under stirring. After stirring for 10 minutes, 14.5 g of cerium acetate, 67 g of zirconium acetate, and 147 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 minutes (particle size D50 = 5-6 μm) and then the pH was adjusted to 3.5-4.0 to prepare a bottom slurry F.

[0065] 921 g of pure water was added with 16.4 g of strontium acetate, and the previously prepared C and D were added under stirring. After stirring for 10 min, 55.9 g of zirconium acetate and 184 g of the previously prepared E were added in sequence. The mixture was placed in a grinder and ground for 15 min (particle size D50 = 5-6 μm), and then the pH was adjusted to 3.5-4.0 to obtain the upper slurry G.

[0066] A Φ20mm*30mm*300 mesh metal support was coated with bottom slurry F at a wet weight gain of 164 g / L. The support was dried at 150°C with air blast. After cooling, the top slurry G was coated at a wet weight gain of 205 g / L. The support was heated to 550°C in air at a rate of 3°C / min and calcined for 3 hours to obtain sample HC-4 for testing.

[0067] Verification Test:

[0068] The performance test of the metal honeycomb catalyst was conducted using the TWC-Catalyst Activity Evaluation System. The catalyst activity evaluation system equipment complies with the requirements of GB / T18377 and QC / T752-2006. The ignition temperature characteristic test was conducted on the TWC-Catalyst Activity Evaluation System using the gas distribution method.

[0069] Test parameter settings: gas concentration CO-4%, NO-300ppm, C3H8-400ppm, O2-2.16%, CO2-10%, balance N2, oxygen balance coefficient λ = 0.97-1.03, control airspeed = 40000±1000h -1 The catalyst inlet temperature was raised from room temperature to 100°C at a rate of 13°C / min to 420±10°C, and the T50 and C400 values ​​were recorded. T50 is the temperature required to achieve 50% pollutant conversion, reflecting the catalyst's low-temperature ignition performance. C400 is the catalyst's pollutant conversion efficiency, expressed as a percentage, at a catalyst inlet temperature of 400°C.

[0070] The test results are shown in Table 1:

[0071]

[0072] Table 1 Catalyst activity evaluation results

[0073] Analysis of the test results above demonstrates that the metal honeycomb-supported catalysts produced using the present invention offer significant advantages in low-temperature ignition activity and pollutant conversion efficiency. These performance reliability and stability are maintained even when using less precious metal. By optimizing the precious metal formulation and creating a synergistic effect to reduce precious metal usage, the goal of improving product performance, reducing costs, and conserving valuable resources can be achieved.

[0074] The present invention improves the low-temperature ignition effect of a metal-supported catalyst, thereby significantly reducing the catalyst's ignition temperature and exhibiting excellent pollutant conversion performance. Specifically, the present invention includes a double-layer slurry preparation method, a double-coating coating process, and process control. The bottom coating comprises at least one precious metal, platinum and palladium, in a specific ratio, and is loaded onto a composite cerium-zirconium powder or a γ-Al2O3 substrate material in a specific manner. The top coating comprises a combination of at least two precious metals, platinum, palladium, and rhodium, and is loaded onto a composite CeO2 or γ-Al2O3 substrate material in a specific manner. Furthermore, the total precious metal content is 3 to 25 g / cft. 3 , the mass ratio of Pt / Pd / Rh is 2~20:5~15:1~2; the coating of metal honeycomb carrier is easy to operate, the process can be quantified and standardized, which is suitable for industrial mass production, and has a wide range of applications in low-temperature cold start emission control of gasoline vehicles and after-sales modified vehicle market.

[0075] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the foregoing embodiments. The foregoing embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions, characterized by: The following steps are involved: Applying a bottom coating and an upper coating on the surface of the metal honeycomb carrier substrate in sequence; The bottom coating comprises composite cerium-zirconium oxide, γ-Al2O3, noble metal active components Pt and / or Pd, hydrosol and strontium acetate; The upper coating layer comprises composite cerium-zirconium oxide, γ-Al2O3, at least two of the noble metal active components Pt, Pd and / or Rh, a hydrosol and strontium acetate; The coated metal honeycomb carrier is dried and calcined to obtain the catalyst.

2. The method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions according to claim 1, characterized in that: The slurry preparation of the bottom coating and the upper coating comprises the following steps: The composite cerium-zirconium oxide, γ-Al2O3 and aqueous sol dispersion are mixed and ground to form a carrier dispersion; Loading the noble metal active component solution into the carrier dispersion to prepare a bottom slurry and an upper slurry respectively; The total amount of precious metals in the bottom slurry accounts for 20-50% wt of the total amount of precious metals in the catalyst, and in the upper slurry accounts for 50-80% wt.

3. The method for preparing a catalyst for improving the low-temperature ignition performance of gasoline vehicle emissions according to claim 2, characterized in that: The hydrosol dispersion is a modified aluminum substrate hydrated colloid with a mass concentration of 5 to 15% wt and accounts for 5 to 15% wt of the total mass of the bottom slurry and the upper slurry.

4. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 1, characterized in that: The bottom coating has an oxide solid content of 35-38% wt, comprising: 0.5-2% wt strontium acetate, 38-85% wt composite cerium-zirconium oxide, 15-60% wt γ-Al2O3, 1-5% wt cerium acetate, 5-12% wt hydrosol, and 0.1-2% wt Pt and / or Pd; The upper coating has an oxide solid content of 25 to 33% wt and comprises: 0.5-2% wt strontium acetate, 38-85% wt composite cerium-zirconium oxide, 15-60% wt gamma-Al2O3, 6-15% wt aqueous sol, and 0.1-3% wt at least two of Pt, Pd, and Rh.

5. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 4, characterized in that: The mass ratio of the components of the composite cerium-zirconium oxide is: CeO2 20-60%, ZrO2 40-70%, La2O3 3-6%, Nd2O3 0-5%, and Y2O3 2-5%.

6. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 4, characterized in that: The mass ratio of the gamma-Al2O3 components is: La2O3 2-10%, Al2O3 90-98%.

7. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 2, characterized in that: The oxide loading amount of the bottom layer slurry coated on the metal honeycomb carrier is 60-100 g / L, the oxide loading amount of the upper layer slurry coated is 50-90 g / L, and the total coating oxide amount is 110-180 g / L.

8. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 2, characterized in that: The noble metal active component is loaded onto the composite cerium zirconium oxide and γ-Al2O3 carrier by a drip leaching method, and the noble metal in the bottom slurry is a single component of Pt or Pd, and the upper slurry is a combination of at least two of Pt, Pd, and Rh.

9. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 2, characterized in that: The bottom layer slurry and the upper layer slurry further contain zirconium acetate, and the proportion of zirconium acetate oxide in the bottom layer coating and the upper layer coating is 1 to 5% by weight.

10. The method for preparing a catalyst for improving low-temperature ignition performance of gasoline vehicle emissions according to claim 1, characterized in that: The calcination treatment conditions are: drying temperature 80-150° C., calcination temperature 400-600° C., and calcination time 2-6 hours.